User's adoption of mobile technologies and applications in the context of medical and nursing students of a Malaysian University - Wong, Yi Lin (Universiti Malaysia Sarawak, (UNIMAS), 2012)
It was argued in the literature that influencing healthcare practitioners'behaviours to accomodate the new ways of working is a necessary step in any new intervention program that tagets to imporve care and health outcomes. Today, the development of mobile healthcare and applications (MTAs) has been one of such initiatives to accomodate the changing landscape of the healthcare industry in delivering health services. Subtantial evidence of the benefits of MTAs has been reported in the literature. Yet there is still very little research has been done to examine the adoption of MTAs and what are the benefits of using MTAs on the context of Malaysian healthcare providers and practitioners.